2021
DOI: 10.3390/ijerph18147572
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Active Rehabilitation Camp on Physical Performance of Disabled People Moving in Wheelchairs

Abstract: (1) Background: Regular participation in physical activity (PA) prevents many medical complications and improves the physical fitness of people with spinal cord injury, and in turn improves the functional independence, psychosocial status and quality of life. The goal of Active Rehabilitation Camps (ARCs) is to use various forms of PA in order for the participants to obtain the greatest efficiency and independence in everyday life. (2) Purpose: To evaluate the improvement in physical performance of people with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
1
3
0
1
Order By: Relevance
“…Additionally, studies by Fliess-Douer confirm that physical activity significantly improves functional status and, as a result, movement [34]. Similar results were presented by Lipert, emphasizing a positive influence of movement and active rehabilitation camps on functional status (with regard to daily activities and movement) of subjects after cervical spinal cord injury [35]. Our own results are different from the results achieved by Nas, where only a slight improvement was observed in such activities as dressing up and using the toilet without assistance [26].…”
Section: Discussionsupporting
confidence: 74%
“…Additionally, studies by Fliess-Douer confirm that physical activity significantly improves functional status and, as a result, movement [34]. Similar results were presented by Lipert, emphasizing a positive influence of movement and active rehabilitation camps on functional status (with regard to daily activities and movement) of subjects after cervical spinal cord injury [35]. Our own results are different from the results achieved by Nas, where only a slight improvement was observed in such activities as dressing up and using the toilet without assistance [26].…”
Section: Discussionsupporting
confidence: 74%
“…This was further supported by Sol et al (2021) in their 2021 study of 60 MWU, concluding from their examination of different training and rehab methods that "A combination of exercise and [Wheelchair Mobility Skills] WMS training appears to have significant positive long-term effects on [physical activity] PA, WMS, confidence in wheelchair mobility, and (an)aerobic performance in youth using a manual wheelchair." Another example of using rehabilitation to promote physical fitness in MWU was given by Canori et al (2023) survey of 26 participants which found that improving a patient's CP could "potentially improve motivation for PA." The preservation of physical fitness was shown to be achievable through active rehabilitation in Lipert et al (2021) study of how rehabilitation affected physical performance for their 42 MWU participants.…”
Section: Physical Fitnessmentioning
confidence: 99%
“…These sessions target prevention of pressure sores/ulcers, prevention of urinary tract infections, bowel management, and sexuality and fertility disorders. This peer-based program has been introduced in more than twenty countries in Europe, Africa, and Asia [34][35][36][37].…”
Section: Practical Implicationsmentioning
confidence: 99%